2006
DOI: 10.1007/s10886-006-9151-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Induced Volatile Emissions among Rice Varieties Result in Differential Attraction and Parasitism of Nilaparvata lugens Eggs by the Parasitoid Anagrus nilaparvatae in the Field

Abstract: We compared the volatiles of JA-treated plants of six rice varieties and then determined, in the laboratory and field, if they differed in attractiveness to Anagrus nilaparavate Pand et Wang, an egg parasitoid of rice planthoppers. Analyses of volatiles revealed significant differences among varieties, both in total quantity and quality of the blends emitted. On the basis of these differences, the six varieties could be roughly divided into three groups. In a Y-tube olfactometer, female wasps preferred odors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 36 publications
(39 reference statements)
3
80
0
7
Order By: Relevance
“…The cereal aphid specialist Aphidius rhopalosiphi was able to distinguish between different cultivated varieties of winter wheat in a Y-tube olfactometer (Wickremasinghe and van Emden, 1992). Different responses of parasitic wasps to different cultivated varieties infested by the same host species have also been reported in larval parasitoids and egg parasitoids (Elzen et al, 1986;Hoballah et al, 2002;Lou et al, 2006). Since we were unable to import into Japan broad 26 H. TAKEMOTO et al bean plants cv.…”
Section: Discussionmentioning
confidence: 96%
“…The cereal aphid specialist Aphidius rhopalosiphi was able to distinguish between different cultivated varieties of winter wheat in a Y-tube olfactometer (Wickremasinghe and van Emden, 1992). Different responses of parasitic wasps to different cultivated varieties infested by the same host species have also been reported in larval parasitoids and egg parasitoids (Elzen et al, 1986;Hoballah et al, 2002;Lou et al, 2006). Since we were unable to import into Japan broad 26 H. TAKEMOTO et al bean plants cv.…”
Section: Discussionmentioning
confidence: 96%
“…Intraspecific variation of herbivore-induced volatile emissions has been reported primarily from varieties of cultivated plants (Loughrin et al, 1995;Geervliet et al, 1997;Gouinguene et al, 2001;Degen et al, 2004;Lou et al, 2006) but has been the subject of only a few investigations of wild species such as solanaceous plants (Halitschke et al, 2000;Glawe et al, 2003;Hare, 2007;Delphia et al, 2009) and teosinte (Gouinguene et al, 2001). In this study, we conducted a survey of 27 Arabidopsis accessions for volatiles released upon treatment with coronalon, a synthetic mimic of octadecanoid plant hormones that induces volatile blends similar to those emitted upon insect feeding (Schuler et al, 2001;Herde et al, 2008).…”
Section: Elicitor-and Insect-induced Volatile Emissions Vary Among Armentioning
confidence: 99%
“…It has been reported that herbivores induce host plants to produce an array of volatile organic compounds and that some of these compounds may be used as chemical cues by natural enemies of herbivores to locate of their prey [6,[17][18][19][20]. A similar phenomenon has also been found in the tritrophic system of the host plant, Bunge prickly ash (Zanthoxylum bungeanum Maxim (Rutaceae)), the herbivore, mealybug (Phenacoccus azaleae (Kuwana) (Hemiptera: Coccoidea: Pseudococcidae)) and the predator, ladybeetle (Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae)).…”
Section: Discussionmentioning
confidence: 99%